Metal-Halogen Interactions Inducing Phase Separation for Self-Healing and Tough Ionogels with Tunable Thermoelectric Performance - Zhao, Wei (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Authors. Advanced Materials published by Wiley‐VCH GmbH.